Microbial Diversity in Soil under Potato Cultivation from Cold Desert Himalaya, India. (3rd September 2013) - Sati, Priyanka; Dhakar, Kusum; Pandey, Anita
Abstract : Mana village (Chamoli district, Uttarakhand, India), situated in high altitudes (3, 238 m above mean sea level) of Indian Himalayan region, represents cold desert climatic conditions. At Mana, potato is grown from May to September, while the site remains snow clad for approximately six months (from October to April). Soil samples, collected from Mana potato fields, were analyzed for cultivable microbial diversity along with the chemical and enzymatic properties. The analysis revealed colonization of soil by microflora in moderate numbers (up to 10 7  CFU/g soil) with limited species level. 25 morphologically distinct microbial isolates belonging to Gram +ve and Gram −ve bacteria, actinomycetes, and fungi including yeast were isolated. The bacteria were tentatively identified as species of Bacillus and Pseudomonas, while the majority of the fungal isolates belonged to the species of Penicillium . These microbial isolates possessed plant growth promotion and biocontrol properties assessed mainly in terms of production of indole acetic acid and hydrolytic enzymes and phosphate solubilization. The soil, when used as "inoculum" in plant based bioassays, exhibited positive influence on plant growth related parameters. The limited diversity of cold tolerant microbial species also extends opportunity to understand the resilience possessed by these organisms under low temperature environment.